Coded communities: organizing boundless diversity - Milburn, Trudy A. (Annals of the International Communication Association, 2021)
Communication researchers have used speech codes theory to interpret local conduct. This qualitative meta-analysis draws upon twenty years of peer-reviewed journal articles and books (2000–2019) that specifically use the concept of speech community within research about speech codes. Although speech community is incorporated into one of the six main tenets of speech codes theory, the concept has not been used consistently. After reviewing how speech codes theory researchers use the concept of speech community, I draw comparisons between those who describe mediated and intercultural practices to interrogate the a priori assertion of a speech community. I conclude by arguing that one must understand the particular social relations among speakers before asserting the existence of a speech community. © 2021 International Communication Association.
2 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed; ⛔ No DOI found